The Effect of Alimony Reform on Married Women's Labor Supply: Evidence from the American Time Use Survey - Daniel Fernández-Kranz; Jennifer Louise Roff (Institute of Labor Economics (IZA), 2021)
Reforms that reduce alimony can affect married couples in two different ways. First, reduced alimony lowers the bargaining power of the payee, usually the wife. Second, reduced alimony lowers the incentives of wives to engage in the traditional male breadwinner model of household specialization. Using the American Time Use Survey and exploiting a series of recent reforms in several US states that reduced the entitlements of eligible spouses, we find that wives surprised by the reforms reacted by moving away from the traditional male breadwinner model of household specialization. We also find that highly educated women substituted work for time devoted to housework and childcare, while less educated wives substituted work for leisure and personal time. We find no effects for men. The fact that the reforms reduced fertility only among women with higher education suggests that the difference between them and less educated wives in the response to reduced alimony is due, at least in part, to differences in their preferences and costs for children. The estimated effects are larger among couples with a large difference in the earnings potential of spouses and are robust to several sensitivity tests.
Keywords: J12; J22; K36; 330; alimony; marriage; time use; labor supply